Effect of Canola Oil and of Beef Fat Coated Commercial Extruded Diets on Growth Performance of Red Hybrid Tilapia (Mutant Pink Nile Tilapia Oreochromis niloticus e X Wild Blue Tilapia 0. aureus y) Juveniles - Appelbaum, S.; Jesu Arockiarar, A. (Malaysian Journal of Science, 2008)
A 45 (lay feeding trial was conducted to evaluate the effect of canola oil and of beef fat coated commercial extruded diet on the growth performance of red hybrid tilapia (mutant pink Nile tilapia Â°reach/inky niloricus ,4" X wild blue tilapia 0. mucus ?) juveniles. The red hybrid tilapia with initial weight ranges between 2.4 and 3.4 g were reared in a fresh water re -circulation system (water flow: 0.5 Limin) at 30Â° C and 0.2 - 0.4 ppt temperature and salinity respectively. The extiuded diet that was coated with three different concentrations viz., 5%, 10% and 20% of canola oil and of beef fat. The canola oil and heel fat coated diets were given ad libitum to red hybrid tilapia at 09.00, 13.00 and 17.00 h daily. The control diet was not sprayed with any lipid sources. All the treatments showed better survival (100%). The best specific growth rate (P < 0.05) and feed conversion ratio were observed in the 5% canola oil coated diet. When comparing the canola oil and beef fat coated diets, canola oil coated diets performed better than the beef fat coated diets on fish